A model for simulating adaptive, dynamic flows on networks: Application to petroleum infrastructure. (January 2018) - Corbet, Thomas F.; Beyeler, Walt; Wilson, Michael L.; Flanagan, Tatiana P.
Highlights: We describe a model of adaptive responses of infrastructure networks to disruptions. We model commodity flows as diffusion with nonlinearities imposing capacity limits. Behavioral parameters govern responses to perturbations via market transactions. A wide range of system responses can be covered using parameters of the model. We illustrate scalability through application to the U.S. petroleum infrastructure. Abstract: Simulation models can improve decisions meant to control the consequences of disruptions to critical infrastructures. We describe a dynamic flow model on networks purposed to inform analyses by those concerned about consequences of disruptions to infrastructures and to help policy makers design robust mitigations. We conceptualize the adaptive responses of infrastructure networks to perturbations as market transactions and business decisions of operators. We approximate commodity flows in these networks by a diffusion equation, with nonlinearities introduced to model capacity limits. To illustrate the behavior and scalability of the model, we show its application first on two simple networks, then on petroleum infrastructure in the United States, where we analyze the effects of a hypothesized earthquake.